Oxygen supersaturated fluid using fine micro/nanobubbles - Matsuki N (Dove Medical Press, 2014)
Noriaki Matsuki,1 Takuji Ishikawa,2 Shingo Ichiba,3 Naoki Shiba,3 Yoshihito Ujike,3 Takami Yamaguchi4 1Department of Biomedical Engineering, Graduate School of Engineering, Okayama University of Science, Okayama, 2Department of Bioengineering and Robotics, Graduate School of Engineering, Tohoku University, Sendai, 3Department of Emergency and Critical Care Medicine, Okayama University Hospital, Okayama, 4Graduate School of Biomedical Engineering, Tohoku University, Sendai, JapanAbstract: Microbubbles show peculiar properties, such as shrinking collapse, long lifetime, high gas solubility, negative electric charge, and free radical production. Fluids supersaturated with various gases can be easily generated using microbubbles. Oxygen microbubble fluid can be very useful for oxygen delivery to hypoxic tissues. However, there have been no reports of comparative investigations into adding fluids containing oxygen fine micro/nanobubbles (OFMNBs) to common infusion solutions in daily medical care. In this study, it was demonstrated that OFMNBs can generate oxygen-supersaturated fluids, and they may be sufficiently small to infuse safely into blood vessels. It was found that normal saline solution is preferable for generating an oxygen-rich infusion fluid, which is best administered as a 30-minute intravenous infusion. It was also concluded that dextran solution is suitable for drug delivery substances packing oxygen gas over a 1-hour intravenous infusion. In addition, normal saline solution containing OFMNBs was effective for improving blood oxygenation. Thus, the use of OFMNB-containing fluids is a potentially effective novel method for improving blood oxygenation in cases involving hypoxia, ischemic diseases, infection control, and anticancer chemoradiation therapies.Keywords: microbubble, fine micro/nanobubble, nanobubble, oxygenation, fluid oxygenation